Analisis Metode Weighted Product dalam menentukan Order Barang Terbaik pada Marketplace Shopee - Dodi Guswandi; Hadi Syahputra; M. Hafizh; Rita; Devia Kartika (Universitas Putra Indonesia YPTK Padang, 2022)
Ordering goods online on the Marketplace is a very popular public habit today because it is very easy to use which can save time, cost, and effort. One of the most visited Marketplaces by customers is the Shopee Marketplace, in this Marketplace, many customers have difficulty determining the best item because the same item is available in several stores with different characteristics, so many ordered items do not match what they expect. This study aims to apply an analytical model in determining the best order for goods on the Shopee Marketplace using a Decision Support System (SPK) with the Weighted Product (WP) method. The performance of the WP method is able to perform weighted multiplication on each criterion after being ranked and the decision results in the form of ranking produce solutions in determining the best order for goods on the Shopee Marketplace. The criteria used to consist of Price (C1), Product Quality (C2), Online Customer Reviews (C3), Number of Goods Sold (C4), Delivery Time (C5), Payment System (C6), and Shipping Discounts (C7). The results of this study which are presented in the performance of the WP method are able to determine the highest value of goods in several stores in the same type of goods, after the ranking results, namely Item A, Store 5, get a value of 0.130237 as the best order of goods.